Differences in stomatal sensitivity to CO2 and light influence variation in water use efficiency and leaf carbon isotope composition in two genotypes of the C4 plant Zea mays - Crawford, Joseph D (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For commercial re-use, please contact reprintsoup.com for reprints and translation rights for reprints. All other permissions can be obtained through our RightsLink service via the Permissions link on the article page on our site—for further information please contact journals.permissions@oup.com.